2001
DOI: 10.1016/s0022-5347(05)65758-8
|View full text |Cite
|
Sign up to set email alerts
|

Spermatic Cord Sarcoma: Outcome, Patterns of Failure and Management

Abstract: Spermatic cord sarcoma has a high propensity for local recurrence after surgery. Nodal relapse is less frequent than commonly believed. Because of the relatively high local failure rate seen in surgery alone and durable local control noted in 3 patients treated with surgery plus radiotherapy, combined modality treatment should be considered in those with spermatic cord sarcoma who are believed to be at high risk for local failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
106
0
20

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(127 citation statements)
references
References 18 publications
1
106
0
20
Order By: Relevance
“…In the case of primary pure testicular osteosarcoma, inguinal orchiectomy with strict and careful follow-up evaluations appears to be a sufficient treatment. However, the prognosis of testicular osteosarcoma is unclear due to the short follow-up duration (14). Lee et al concluded that primary pure testicular osteosarcoma may be associated with a favorable prognosis (16).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of primary pure testicular osteosarcoma, inguinal orchiectomy with strict and careful follow-up evaluations appears to be a sufficient treatment. However, the prognosis of testicular osteosarcoma is unclear due to the short follow-up duration (14). Lee et al concluded that primary pure testicular osteosarcoma may be associated with a favorable prognosis (16).…”
Section: Discussionmentioning
confidence: 99%
“…Боль-шинство (70,2%) случаев составляют локализованные формы, менее половины (45%) представлены высоко-дифференцированными опухолями. Самым распростра-ненным гистологическим типом оказалась липосаркома (46,4%), следующим по частоте -лейомиосаркома (20%), более редкие -злокачественная гистиоцитома (13%) и рабдомиосаркома (9%) [6][7][8][9][10][11][12][13]. Рабдомиосарко-ма в отличие от других новообразований выявляется преимущественно у молодых пациентов (средний воз-раст 26 лет) и характеризуется агрессивным клиниче-ским поведением -в 30,6% случаев обнаружены регио-нарные и отдаленные метастазы.…”
Section: Abstract: Spermatic Cord Liposarcomaunclassified
“…Низкая дифференциров-ка опухоли, распространенная стадия и поражение лим-фатических узлов достоверно снижают выживаемость [6,8,9].…”
unclassified
See 2 more Smart Citations